PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE TERHADAP HASIL BELAJAR PASSING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS VIII SMPN 1 TAKERAN, KABUPATEN MAGETAN) - ANDRI KUSUMA, ADITYA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract  Physical education is a form of education which uses body movement as a mean and the purpose of education. Through physical education, students are directed to the physical activities including sports ability, one of them is the learning process of underhand pass in volley ball. Based on that matter, the increasing of teaching-learning in physical education at school is needed and the innovation in teaching-learning model which can coop with that problem is also needed. Based on that matter, the researcher is formulating some problems which are whether there is effect and how big is the effect of applying cooperative learning model, Think-Pair-Share, on the learning result of underhand pass volley ball at the students of eighth grade students  of SMP Negeri 1 Takeran Magetan or not. The aim of this research is to know the effect and how big is the effect of applying cooperative learning model, Think-Pair-Share, on the learning result of underhand pass volley ball at the students of eighth grade students  of SMP Negeri 1 Takeran Magetan. This research is an experimental study with using descriptive quantitative approach. Experimental study is a research conducted tightly to find out cause-effect relationship between variables. One of the main characteristics is the existence of treatments given to the subject. in this research, the researcher uses randomized control group pre-test post-test design. The population which is used by the researcher is the eighth grade students  of SMP Negeri 1 Takeran Magetan. This population consist of eight classes.  the sample of this research is the students in VIII C as the experimental group which consist of 32 students and VIII H as the control group which consist of 30 students. Those groups is decided by using  cluster random sampling technique. The rate of improvement for the experimental group before and after the cooperative learning model, Think-Pair-Share applied is 69,76%. Hence, it can be concluded that there is significant influence between the implementation of cooperative learning model type think-pair-share and the learning improvement in volley ball down-pass on the eighth grade students  of SMP Negeri 1 Takeran Magetan. Keywords: learning model, cooperative, think-pair-share, learning result, underhand pass Abstrak Pendidikan jasmani merupakan bentuk pendidikan yang menggunakan aktivitas gerak sebagai sarana dan tujuan pendidikan. Melalui pendidikan jasmani, siswa diarahkan ke dalam aktivitas jasmani termasuk keterampilan olahraga, salah satunya pembelajaran passing bawah bolavoli. Oleh karena itu, perlu adanya peningkatan dalam pembelajaran pendidikan jasmani di sekolah sehingga perlu adanya perubahan model pembelajaran yang dianggap mampu untuk mengatasi kesulitan tersebut. Berdasarkan hal tersebut peneliti merumuskan masalah apakah ada pengaruh dan seberapa besar pengaruh  penerapan model pembelajaran kooperatif tipe think-pair-share terhadap hasil belajar passing bawah bolavoli pada siswa kelas VIII SMP Negeri 1 Takeran Magetan. Penelitian ini bertujuan untuk mengetahui pengaruh dan besarnya pengaruh penerapan model pembelajaran kooperatif tipe think-pair-share terhadap hasil belajar passing bawah bolavoli pada siswa kelas VIII SMP Negeri 1 Takeran Magetan. Jenis penelitian adalah eksperimen dengan pendekatan deskriptif kuantitatif. Penelitian eksperimen adalah suatu penelitian yang dilakukan secara ketat untuk mengetahui hubungan sebab akibat diantara variabel-variabel. Salah satu ciri pokok dari penelitian eksperimen adalah adanya perlakuan (treatment) yang diberikan kepada subyek penelitian Dalam penelitian ini, peneliti menggunakan desain randomized control group pre-test post-test design. Populasi yang digunakan peneliti adalah siswa kelas VIII SMPN 1 Takeran, Magetan  terdiri dari 8 kelas. Sampel penelitian adalah siswa kelas VIII C sebagai kelompok eksperimen yang berjumlah 32 siswa dan kelas VIII H sebagai kelompok kontrol yang berjumlah 30 siswa diambil dengan cara teknik  cluster random sampling. Untuk besarnya pengaruh kelompok eksperimen sebelum dan sesudah penerapan model pembelajaran kooperatif tipe think-pair-share yaitu sebesar 69,76%. Maka dapat disimpulkan bahwa penerapan model pembelajaran kooperatif tipe think-pair-share terdapat pengaruh terhadap peningkatan hasil belajar passing bawah bolavoli pada siswa kelas VIII SMP Negeri 1 Takeran Magetan. Kata Kunci: model pembelajaran, kooperatif, think-pair-share, hasil belajar, passing bawah